Competence in EvidenceBased Medicine among Residents of Kerman University of Medical Sciences Iran - Esmat Nouhi; Ali Akbar Haghdoost; Mehdi Zareiyan; Zohreh Rahaei; Ali Akbar Haghdoost (Kerman University of Medical Sciences, 2014)
Background & Objective: Evidencebased medicine (EBM) is a systematic review process for evaluating and using results of the best clinical trials for diagnosis and treatment of diseases It must comply with the values and specific circumstances of each patient in need of treatment Since very few studies have examined the competence of different groups of medical professionals in this area this study was conducted to assess the competence of residents in EBM   Methods: This descriptive crosssectional study was conducted on 90 residents from 4 main clinical departments in Kerman University of Medical Sciences Iran in 2013 The data collection tool was the Berlin Standard Questionnaire The samples were selected using census method and data were analyzed using SPSS software   Results: Among the participants in the study 422% were male and 578% female with the mean age of 3117 ± 332 years Based on the results of the study residents had little competence in the field of evidencebased medicine their scores ranged from 0 to 8 and their mean score was 254 ± 143 of a total of 15   Conclusion: Considering the mean score and low competence of residents in evidencebased medicine shortterm programs by the relevant departments seem essential to rapidly promote knowledge of evidencebased medicine